INTENSIFIKASI POLA AGROFORESTRI PEKARANGAN DENGAN XANTHOSTEMON sp SEBAGAI TANAMAN PAKAN LEBAH - Yuslinawari; Sofia Rahmawati; Siwi Istiana Dinarti (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Kebondalem Madurejo is one of the villages which is the route that tourists pass from Yogyakarta to the tourist sites of Ijo Temple and Breksi Cliff. The main problem is that this design has an agricultural land area of ​​more than 50% and is the livelihood of the residents. The condition in the form of green land is important as a buffer zone for the nearby tourist complex. Instead of being managed properly, this green land is threatened to become land for land conversion. The function of green land is meant as a buffer zone to support the core area, namely the tourist complex. Based on this background, green land requires knowledge and concrete actions in management in the form of land intensification. The aim of this PkM is to provide education to the public regarding intensification in managing agricultural land and/or those managed with agroforestry through activities with extension and sharing methods. Planting and how to propagate by cuttings are used as demonstration methods to achieve the goal of increasing understanding and awareness of the community in maintaining the management of their yards. The results of this PkM are expected to increase and continue the awareness of residents to intensify the existing green land starting from the yard. This PkM will also produce examples of mini yard plots which will be added with the Xanthstemon sp flower as a plant that has the potential to be used as food for honey bees.